Electron accumulation layer in ultrastrong magnetic field - Sammon, M.; Han Fu; Shklovskii, B.I. (Физика низких температур, 2017)
When a three-dimensional electron gas is subjected to a very strong magnetic field, it can reach a quasi-onedimensional
state in which all electrons occupy the lowest Landau level. This state is referred to as the extreme
quantum limit (EQL) and has been studied in the physics of pulsars and bulk semiconductors. Here we present
a theory of the EQL phase in electron accumulation layers created by an external electric field E at the surface
of a semiconductor with a large Bohr radius such as InSb, PbTe, SrTiO₃ (STO), and particularly
in the LaAlO₃/SrTiO₃ (LAO/STO) heterostructure. The phase diagram of the electron gas in the plane of the
magnetic field strength and the electron surface concentration is found for different orientations of the magnetic
field. We find that in addition to the quasi-classical metallic phase (M), there is a metallic EQL phase, as well
as an insulating Wigner crystal state (WC). Within the EQL phase, the Thomas–Fermi approximation is used
to find the electron density and the electrostatic potential profiles of the accumulation layer. Additionally,
the quantum capacitance for each phase is calculated as a tool for experimental study of these phase diagrams.